Four novel phenanthrene derivatives with α-glucosidase inhibitory activity from gastrochilus bellinus - Htoo Tint San (2022)
Four new phenanthrene derivatives, gastrobellinols A-D (1–4), were isolated from the methanolic extract of Gastrochilus bellinus (Rchb.f.) Kuntze, along with eleven known phenolic compounds including agrostophyllin (5), agrostophyllidin (6), coniferyl aldehyde (7), 4-hydroxybenzaldehyde (8), agrostophyllone (9), gigantol (10), 4-(methoxylmethyl)phenol (11), syringaldehyde (12), 1-(4′-hydroxybenzyl)-imbricartin (13), 6-methoxycoelonin (14), and imbricatin (15). Their structures were determined by spectroscopic methods. Each isolate was evaluated for α-glucosidase inhibitory activity. Compounds 1, 2, 3, 7, 9, 13, and 15 showed higher activity than the drug acarbose. Gastrobellinol C (3) exhibited the strongest α-glucosidase inhibition with an IC50 value of 45.92 µM. A kinetic study of 3 showed competitive inhibition on the α-glucosidase enzyme. This is the first report on the phytochemical constituents and α-glucosidase inhibitory activity of G. bellinus.